Egeria's Views From the Mountain: Female Agency and Biblical Stylization in the Itinerarium Egeriae - Staat, Klazina (Journal of early Christian studies, 2025)
The late fourth-century writer Egeria was a true mountaineer, climbing no fewer than six mountains during her pilgrimage to the lands of the Bible and early Christian history. In her personal account of her pilgrimage, the Itinerarium Egeriae, she provides vivid descriptions of the views from Mount Sinai and Mount Nebo. Contextualized within the wider histories of mountaineering and Latin literacy in Antiquity, it becomes clear that Egeria’s agency as a female mountaineer authoring her own experiences as a viewer from the mountain is highly exceptional. Mountain climbing and the related act of viewing from mountains were mostly male activities in Antiquity. The same pertained to the act of writing in Latin, which was mostly done by men. This article highlights the importance of the Bible in explaining Egeria’s appearance as a woman mountaineer and writer of Latin. Using the narratological distinction of “fabula,” “story,” and “text,” the article demonstrates that the Bible functions not only as Egeria’s guidebook during the pilgrimage, inspiring her mountain climbs at the basic narrative level, but also provides a lens to focalize the landscape and a model for textual composition. Thus, it highlights the unique importance of the Itinerarium Egeriae in the history of gender, literacy, mountaineering, and the gaze in the Latin literary tradition. [End Page 537]